Association of Serum miR-186-5p With the Prognosis of Acute Coronary Syndrome Patients After Percutaneous Coronary Intervention - Li, Zhuoling; Wu, Jia; Wei, Weishi; Cai, Xiaomin; Yan, Jing; Song, Jiaxi; Wang, Cheng; Wang, Junjun (Frontiers in Physiology, 2019)
Circulating miR-186-5p is an emerging biomarker for acute coronary syndrome (ACS) patients. However, its kinetic signatures and prognostic values in ACS patients undergoing percutaneous coronary intervention (PCI) remain unclear. Levels of serum miR-186-5p were determined in 96 healthy controls and 92 ACS patients before and after PCI by qRT-PCR, and the physiologic state of miR-186-5p was analyzed by comparing its absolute concentrations in isolated exosomes and exosome-depleted supernatants. An average of one year of follow-up for ACS patients after PCI was performed. MiR-186-5p levels in the myocardium and serum of rats following left anterior descending coronary artery (LAD) ligation were measured. Serum miR-186-5p levels were found to be significantly increased in ACS patients upon admission compared with those of controls, but these high miR-186-5p levels gradually decreased within one week after PCI. Serum miR-186-5p was mainly present in an exosome-free form rather than membrane-bound exosomes. Within one year of follow-up, ACS patients with higher miR-186-5p levels upon admission exhibited a higher incidence of MACE after PCI. Different statistical analyzes further validated the independent prognostic values of serum miR-186-5p in ACS patients after PCI. Serum miR-186-5p levels in rats following LAD ligation were increased, and there was a decrease in myocardial miR-186-5p levels. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis was performed to predict the related pathways of target genes of miR-186-5p, which suggested that miR-186-5p might be involved in ACS by regulating the inflammatory status and d glucose metabolism. In conclusion, a distinctive expression signature of serum miR-186-5p may contribute to monitoring the clinical condition and assessing the prognosis of ACS patients undergoing PCI.